Factors influencing plantation workers productivity: case study on Boustead Estates Agency Sdn Bhd / Cecilia Rijeg - Rijeg, Cecilia (2008)
Good productivity of workers is very important for any company to contribute a good profit and to improve the workers standard of living where as lower productivity is a problem to the company where more workers need to be employed and higher cost will incurred if production is below expectation. Therefore, with limited resources of workers, productivity must be improved to increase the overall output and profit. The primary objective of this study is to determines what factors will influence plantation workers productivity and how strong each factor will influence workers productivity based on the feedback gathered from the managers, supervisors and the estates workers. Five variables have been identified and tested in this study that are management practices, motivation, training, machine and equipment and working condition. The findings from questionnaires revealed that all the five factors have a positive influence to workers productivity where motivation is the strongest factor influencing workers productivity followed by management practices. Training, Working condition and machine and equipments also will influence productivity although the result shows that the influence is slightly lesser compare to motivation and management practices. Therefore, it is important that the estate management to further improve their management practices while continue motivate workers with good basic accommodation and facility in the estate. The management need to further evaluate the used of machine and equipment in the estate to ensure that it should contribute to higher productivity and where applicable more training need to be conducted to train the workers on the benefit and proper use of machine and equipment and how they can increase productivity when they are equip with better machine and equipments.